198k views
4 votes
Solve the system of equations. (1 point)

2x - 5y = 3
x - 3y = 1
A. (4,1)
B. ( 5,2)
C. ( 7,2)
D. (9,3)

User Lcnicolau
by
4.9k points

2 Answers

6 votes
Solve using elimination method-
Eliminate the x’s

Distribute -2

-2x + 6y = -2

Subtract

2x - 5y = 3
-2x + 6y = -2

y = 1

Plug it in:

x - 3 = 1

x = 4

Solution
(4,1)


confirm:


2(4) - 5(1) = 3
User Chutsu
by
5.4k points
1 vote

Answer: A. (4,1)

Explanation:

2x -5y = 3

x -3y = 1

Change the equation to isolate a variable so you can substitute it in the other one.

x = 1+3y so

2(1+3y) -5y = 3

2 + 6y -5y =3

2 + y = 3

y=1

Back to the easy equation we isolated

x = 1+3(1)

x= 4

(4,1) is a point where x=4 and y=1

User IAmNotARobot
by
4.6k points